1982
DOI: 10.1071/ch9821699
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the Podocarpaceae. LXIV. Studies in the ambergris odorant field

Abstract: The cyclic ethers 17-nor-16-oxa-l3β-kaurane (8) and 15,16-epoxy-17-nor-15,16-seco-8β,13β-kaurane (11) have been prepared from 13 β-kaur-15-ene ('isophyllocladene')(1) and 13 β-kaur-16-ene ('phyllocladene') (2), respectively. The derivative (8), but not (11), possesses an ambergris-type odour. Preparation of the 8 β,12-epoxides (30),(31),(33) and (34) from 12-hydroxypodocarpa-8,11,13-trien-19-oic acid ('podocarpic acid') (3) indicates that substitution of the 4β-methyl group destroys their potentially odorifero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For the intramolecular C 18 acetals 11 and 12 it has been suggested that the triaxial substituents are the 9α-proton, the C-15 methylene group, and the C-13 oxygen atom and that the function of the C-8 oxygen is to simulate part of the decalin ring system (Figure ). Indeed, replacement of the C-8 oxygen functionality by a methylene group yields a cyclic ether 13 which still retains a sweet ambergris odor of moderate intensity . This phenomenon, however, is not universal: the oxalactone 14 has a strong amber odor, whereas its carbon analogue 15 is odorless.…”
Section: Qsar Studies In Specific Odor Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…For the intramolecular C 18 acetals 11 and 12 it has been suggested that the triaxial substituents are the 9α-proton, the C-15 methylene group, and the C-13 oxygen atom and that the function of the C-8 oxygen is to simulate part of the decalin ring system (Figure ). Indeed, replacement of the C-8 oxygen functionality by a methylene group yields a cyclic ether 13 which still retains a sweet ambergris odor of moderate intensity . This phenomenon, however, is not universal: the oxalactone 14 has a strong amber odor, whereas its carbon analogue 15 is odorless.…”
Section: Qsar Studies In Specific Odor Areasmentioning
confidence: 99%
“…[87][88][89] Indeed, replacement of the C-8 oxygen functionality by a methylene group yields a cyclic ether 13 which still retains a sweet ambergris odor of moderate intensity. 90 This phenomenon, however, is not universal: the oxalactone 14 has a strong amber odor, whereas its carbon analogue 15 is odorless. Ohloff's reasoning is that differences in the dielectric polarizations of these two compounds will affect the orientation of these molecules as they approach the receptor membrane.…”
Section: A Ambergrismentioning
confidence: 99%